Writing religious history: the historiography of Ethiopian pentecostalism - Haustein, Jörg (Studien zur außereuropäischen Christentumsgeschichte (Asien, Afrika, Lateinamerika), 2011)
Introduction : parameters for a history of Ethiopian Pentecostalism -- Relating to missionary beginnings : the Finnish and Swedish Pentecostal missions in Ethiopia -- Discovering origins : Ethiopian revival movements and the foundation of a Pentecostal church -- Defining the politics of persecution : Pentecostals in the Ethiopian empire -- Accounting for the underground : persecution and the proliferation of Pentecostalism during the Derg -- Conclusion : writing religious history.